Hubungan Komunikasi Orang Tua Dengan Keberhasilan Anak Tunanetra Usia 10-12 Tahun Membaca Huruf Braille Di SDLB Negeri Kota Malang - Lilla Maria (2019)
Communication of parents greatly influences the way children learn. Parents need to instill the importance of self-confidence in children with these special needs in order to be able to attend education for blind children, one of which is reading braille. The purpose of this study is to determine the relationship between communication between parents and the success of blind children aged 10-12 years reading braille letters in Malang City Public Elementary School. The method in this study used a descriptive research design with a cross-sectional approach. Sampling uses simple random sampling with a total sample of 40 children. Data analysis using chi-square. The results obtained based on statistical tests obtained a value of ρ value 0,000 (